The Personal Development Seminar Handbook. Some Background, Objectives and Helpful Suggestions for Instructors and Students - Weisse, Edward B., Comp.; Bowman, David L., Comp.; Wisconsin Univ., Oshkosh ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This is a manual for the Professional Development Seminar (PDS), a required course for all freshmen and transfer students in the College of Education at the University of Wisconsin, Oshkosh. The manual states the PDS provides a way for beginning students in education to come into academic and social contact with a faculty member in the College of Education. The manual has been designed as a suggestive resource for seminar leaders. It begins with a list of the eight major purposes of the course, and then presents suggestions for class assignments such as (1) topics for reflections by students, (2) activities that will help students get to know one another, (3) ground rules for discussions, and (4) lesson plans on various topics. Also included in the manual are items relating to the past successes of the course, for example (1) a student feedback form, (2) effective strategies used by PDS staff members, (3) a list of field trips and activities, and (4) types of social activities conducted. A list of additional resources is also contained in the manual. (RC)
ERIC Note: For related documents, see SP 009 771.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Students; Course Descriptions; Curriculum Enrichment; Guides; Higher Education; Human Relations; Individual Development; Instructional Materials; Self Actualization; Seminars; Teacher Education; Teacher Education Curriculum; Teacher Response; Professional Development Seminar; Reports, Descriptive